Development of a lightweight grouting composition with a moderate expansion effect - Eshpulatov, T P; Aminov, A M (IOP conference series. Earth and environmental science, 2022)
Typically, oil well cement without additives with a water-cement ratio (WC) of 0.5 at a temperature of 393 K and a pressure of 40 MPa has a shrinkage of up to 0.015% by volume. This is a sufficient value for the formation of a channel between the borehole wall and the outer diameter of the casing string. In this research, Kokdumalak gas and oil field in Uzbekistan was selected as study site. During the experiments, laboratory studies with SAF on the subject of its use for cementing wells as an additive to Portland cement in order to increase the tightness of the cement ring of the production casing, prevent annular gas manifestations during WOC and formation of annular pressure. Comparing the results of physical and mechanical tests of these compositions, it can be noted that the pumpability of the composition containing basalt flour waste was somewhat higher, the end of setting occurs somewhat later (3 hours 50 minutes for 2 composition No. 2 and 4 hours 30 minutes for the composition No. 1).